2011
DOI: 10.4187/respcare.00775
|View full text |Cite
|
Sign up to set email alerts
|

Neurally Adjusted Ventilatory Assist: A Ventilation Tool or a Ventilation Toy?

Abstract: Mechanical ventilation has, since its introduction into clinical practice, undergone a major evolution from controlled ventilation to various modes of assisted ventilation. Neurally adjusted ventilatory assist (NAVA) is the newest development. The implementation of NAVA requires the introduction of a catheter to measure the electrical activity of the diaphragm (EA di ). NAVA relies, opposite to conventional assisted ventilation modes, on the EA di to trigger the ventilator breath and to adjust the ventilatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 35 publications
1
31
0
1
Order By: Relevance
“…9 NAVA triggering was applied when the EAdi reached 0.5 V, and the EAdi signal was measured every 16 ms, both of which are consistent with the application of NAVA in other literature. 6,8 Delisle et al have identified a statistically significant increase in tidal volume variability when supported breaths were flow assisted by NAVA, a finding that is consistent with the conclusions of other recent publications. 6,10 The authors suggest that the greater tidal volume variability measured during NAVA may be associated with the elimination of all central apneas during non-rapid-eye-movement sleep in their study.…”
supporting
confidence: 86%
See 4 more Smart Citations
“…9 NAVA triggering was applied when the EAdi reached 0.5 V, and the EAdi signal was measured every 16 ms, both of which are consistent with the application of NAVA in other literature. 6,8 Delisle et al have identified a statistically significant increase in tidal volume variability when supported breaths were flow assisted by NAVA, a finding that is consistent with the conclusions of other recent publications. 6,10 The authors suggest that the greater tidal volume variability measured during NAVA may be associated with the elimination of all central apneas during non-rapid-eye-movement sleep in their study.…”
supporting
confidence: 86%
“…[3][4][5][6] Considering a current healthcare context that is increasingly concerned with safety, clinically important patient outcomes, and cost containment, I believe that the use of NAVA has not yet been adequately justified in the literature. What is the clinical importance of this study; the "So what?"…”
Section: See the Original Study On Page 745mentioning
confidence: 99%
See 3 more Smart Citations